ANALISIS ISI BERITA PEMBANGUNAN FLY OVER SIMPANG JAM KOTA BATAM DI WEBSITE BATAMPOS.CO.ID (STUDI ANALISIS DESKRIPTIF KEBERIMBANGAN BERITA) - Prasetyo, Anggi; Abidin, Sholihul (SCIENTIA JOURNAL, 2019)
Research is called “Content Analysis Of Fly Over Development News Simpang Jam Of Batam City In BatamPos.Co.Id Website (Study Of Cover Both Side Analysis)”. The purpose of this study to know cover both side the news of the flyover simpang jam the city of Batam on the topic of news, the subject of news, the news, and the type of news. The study with the quantitative sort of descriptive set on analysis contents of the model Holsti, this study aims to know cover both side the flyover news, published by online media www.batampos.co.id. The research taken from the news of the flyover period October 2015 – June 2017, as much as 7 news. The study conclude that the flyover news in the online media www.batampos.co.id is balanced from the aspect of the topic of news, the subject of news, the news, and the type of news. But, still must be considered more mistakes in writing that need to be corrected before publication.